POTENSI FRAKSI n-HEKSAN EKSTRAK ETANOL RIMPANG LENGKUAS [Alpinia galanga (L.) Swartz.] DALAM MENINGKATKAN KUALITAS SPERMA DAN SPERMATOGENESIS - Yance Anas; Imam Faozi; Suharjono Suharjono (Jurnal Ilmu Farmasi dan Farmasi Klinik, 2017)
ABSTRACT Flavonoids and steroid's compounds have been identifying in the galangal rhizome [Alpinia galanga (L.) Swartz.]. This compound has hormonal and antioxidant effects and can improve the spermatogenesis and quality of spermatozoa. The purpose of this study is to find out the effects of the n-hexane fractions from galangal rhizome ethanol extract (HFGREE) on male Swiss mice spermatogenesis and quality of spermatozoa. This research is a laboratory experimental with randomized matched post test only controls group design. Twenty-four male Swiss mice (8-weeks old) divided among four groups: control groups (mice treated with CMC 1.0% 10 mL.kg-1.day-1), and three groups of mice treated with HFGREE (1.29; 2.58 and 5.16) mg.kg-1.day-1 for 30 days. All mice sacrificed at day 31. Furthermore, testicular tissue sections are used to calculate the score of spermatogenesis. Spermatozoa in the epididymis were used to assess the quality of spermatozoa. The results showed the HFRGEE (2.58 and 5.16) mg.kg-1.day-1 for 30 days, significantly elevate spermatogenesis score, and improve the spermatozoa count, spermatozoa motility, healthy and normal spermatozoa of male Swiss mice (p<0.05). Further studies can focus on the identification of active compounds in HFGREE that play a role in improving spermatogenesis and quality of spermatozoa. Key words: n-hexane fraction, galangal rhizome ethanol extract, spermatogenesis, quality of spermatozoa